An efficient crime group of secured data sharing scheme in cloud - Rashid, Mustafa Noori (2018)
The importance of cloud computing is the users can accomplish an effective and economical approach for data sharing among group members in the cloud with the characteristics of low maintenance and little management cost. Cloud security is a part of computer security. Data confidentiality requires that unauthorized users including the cloud are incapable of learning the content of the stored data. Maintenance of the availability of data confidentiality for dynamic groups is still an important and challenging issue. The cloud provider cannot be treated as a trusted third party (cloud storage services) because of its semi-trust nature, and thus the traditional security models cannot be straight forwardly generalized into cloud based group sharing frameworks. We propose a crime group of information sharing framework for cloud, which can effectively take advantage of the cloud servers' help but have no sensitive data being exposed to attackers and the cloud provider. By applying the proxy signature technique, the group leader can effectively grant the privilege of group management to one or more chosen group members. By adopting proxy re-encryption, most computationally intensive operations can be delegated to cloud servers without disclosing any private information. Extensive security and performance analysis shows that our proposed scheme is of high efficiency and satisfies the security requirements for public cloud-based secure groups.